Total phenol, flavonoid, and anthocyanin content and antioxidant activity of Etlingera elatior extract and nanoparticle - Lestari, Tresna; Nofianti, Tita; Tuslinah, Lilis; Ruswanto, Ruswanto (Pharmaciana, 2018)
Despite the long and wide application, traditional medicine is known for its minimum efficacy. Nanoparticle technology has reported to optimally address this weakness by enhancing the ability of the medicine to penetrate the biological membrane and, thereby, increasing the absorption. In this research, Etlingera elatior (ginger flower) extract, which has antioxiandt activity, was formulated into nanoparticles with ionotropic gelation method using chitosan (0.08, 0.09, 0.1, 0.2, and 0.3%) and 0.01% NaTPP. The nanoparticles were characterized by their particle size, polydispersity index, zeta potential, and entrapment efficiency against total phenolic compound, flavonoid, and anthocyanin. The ones with the best properties were then analyzed with Scanning Electron Microscopic (SEM) method and tested for its antioxidant activity against DPPH. The results showed that all of the formula variations produced particle size in the range of 147.0-566.2 nm with a polydispersity index of < 0.5 and zeta potential between 0.45-45.90 mV. Also, the absorption efficiencies of phenol, flavonoid, and anthocyanin were 72.62-84.24%, 55.18-92.05%, and 75.67-97.96%, respectively. Overall, the best characteristics were presented by the combination of 0.1% chitosan and 0.01% NaTPP, which produced 246.4-nm nanoparticles with a polydispersity index of 0.418, and zeta potential of 26.60 mV. These nanoparticles also contained phenol, flavonoid, and anthocyanin with good absorption efficiencies, namely 78.5186%, 92.05%, and 97.96%, respectively. SEM analysis showed that these nanoparticles were round and had a soft surface. The radical scavenging activities of the extract and the nanoparticles against DPPH, as presented by the IC50 values, were 19.614 ppm and 160 ppm.